Determination of Tourists' Choice in Determining Destinations in Garut Regency - sopiah, sopiah; Nurhasan, Rohimat (Journal of Research in Social Science and Humanities, 2025)
Garut Regency in West Java has an extraordinary tourism potential, with a variety of options such as beautiful mountains such as Papandayan and Guntur, beautiful beaches in the south such as Sayang Heulang and Santolo, plus natural hot springs in Cipanas that make people feel at home soaking up. Not to mention the rich local culture, ranging from typical dodol to handicrafts that can be unique souvenirs. But, even so, there is still a gap in our understanding of what makes tourists choose Garut as their destination—this is very important to encourage the development of the tourism sector there, which can be a support for the local economy. This study tries to dig deeper into the main factors that influence tourists' decisions, using a simple but powerful quantitative method, namely exploratory factor analysis to group variables and logistical regression to see how much influence it has. Data was taken from a direct survey of 100 tourists who were sightseeing in Garut's hit spots, such as Mount Papandayan, Sayang Heulang Beach, Situ Bagendit, Sindangkasih Tourism Village, and Cipanas, the majority of them were domestic tourists who were looking for affordable natural recreation. The results show that there are six key factors that come out: natural attractions and tourism that are the main stars, accessibility and supporting facilities, costs and prices that must be pocket-friendly, social interaction plus local culture, the reputation of the destination from people's reviews, and the diversity of activities such as hiking or outbound that make you not bored. The most dominant is natural attraction, which can explain about 35% of the total variance—that is, the natural beauty of Garut is really a strong magnet for attracting visitors. These findings provide practical implications for tourism managers and local governments, for example increasing digital promotion so that more people know, improving road infrastructure to make access easier, or developing cheap tour packages that combine nature with local culture.